Neurophysiological and Behavioral Responses of Mandarin Lexical Tone Processing - Yu, Yan H.; Shafer, Valerie L.; Sussman, Elyse S. (Frontiers in Neuroscience, 2017)
Language experience enhances discrimination of speech contrasts at a behavioral- perceptual level, as well as at a pre-attentive level, as indexed by event-related potential (ERP) mismatch negativity (MMN) responses. The enhanced sensitivity could be the result of changes in acoustic resolution and/or long-term memory representations of the relevant information in the auditory cortex. To examine these possibilities, we used a short (ca. 600 ms) versus long (ca. 2600 ms) interstimulus interval (ISI) in a passive, oddball discrimination task while obtaining ERPs. These ISI differences were used to test whether cross-linguistic differences in processing Mandarin lexical tone are a function of differences in acoustic resolution and/or differences in long-term memory representations. Bisyllabic nonword tokens that differed in lexical tone categories were presented using a passive listening multiple oddball paradigm. Behavioral discrimination and identification data were also collected. The ERP results revealed robust MMNs to both easy and difficult lexical tone differences for both groups at short ISIs. At long ISIs, there was either no change or an enhanced MMN amplitude for the Mandarin group, but reduced MMN amplitude for the English group. In addition, the Mandarin listeners showed a larger late negativity (LN) discriminative response than the English listeners for lexical tone contrasts in the long ISI condition. Mandarin speakers outperformed English speakers in the behavioral tasks, especially under the long ISI conditions with the more similar lexical tone pair. These results suggest that the acoustic correlates of lexical tone are fairly robust and easily discriminated at short ISIs, when the auditory sensory memory trace is strong. At longer ISIs beyond 2.5 s language-specific experience is necessary for robust discrimination.